MARKETING ANALYTICS IN THE ERA OF DIGITAL-BASED MARKETING STRATEGY - Hidayati, Arifah; Susanti, Evi; Jamalong, Ahmad; Ginting, Dafid; Suwanto, Witri; Arifin, Ardian (LPPM Universitas Jambi, 2024)
This groundbreaking study delves into the intricate realm of digital marketing analysis, which entails the systematic collection and scrutiny of data pertaining to digital marketing endeavors. With a novel focus on elucidating the economic ramifications of digital marketing on sales augmentation, the research employs an innovative approach. Leveraging an exhaustive literature review drawn from national and international journals, the study illuminates the transformative impact of digital marketing, particularly in the context of burgeoning online markets. Employing the PRISMA methodological framework, researchers meticulously navigated through the identification, screening, feasibility, and finalization phases to distill a comprehensive understanding of the topic's scope. With a laser focus on